Implant Volume Loss, Misfit, Screw Loosening, and Stress In Custom Titanium and Zirconia Abutments - Barbosa Jr,Sales Antônio (2020)
Abstract The aim of this study was to verify the effect of the implant volume loss, vertical misfit between abutment and prosthetic platform, prosthetic screw loosening torque, and screw stress distribution in titanium and zirconia abutments. Ten CAD/CAM system custom abutments of each material were milled and attached to the titanium implants. The implant volume loss was evaluated by microtomography, the vertical misfit with optical microscopy, and digital torque wrench measured the prosthetic screw loosening. All experimental analyses were performed before and after mechanical cycle (1,000,000 cycles, 100 N/2 Hz). Virtual models of the structures were created for finite element analysis, and the stress on the screw obtained with von Mises procedure. Data were analyzed using an independent t-test, two-way ANOVA for repeated measures, and Tukey’s HSD test (a=0.05). There was no significant difference in the implant volume loss for the two abutment materials (p=0.662). Titanium abutments provided higher loosening torque values after mechanical cycling (p<0.001). Lesser marginal misfit was obtained with titanium abutments before and after mechanical cycling (p<0.001). The stress distribution on the screw was similar between abutment materials. In conclusion, CAD/CAM custom titanium abutment reduced the marginal misfit and increased the torque maintenance of prosthetic screws when compared to CAD/CAM custom zirconia abutment.